Integrated chemical looping combustion in pulp mill for high energy efficiency and low carbon emission. (1st December 2020) - Man, Yi; Hu, Song; Gao, Jieqi; Li, Jigeng; Hong, Mengna
Abstract: Pulp making is a high-energy-consumption process that obtains its energy by directly combusting coal and black liquor in boiler, which is low efficiency and high emission. Mini-sulfide sulfite anthraquinone (MSSAQ) pulp making technology can reach 55%–66% pulping yield but suffers from bad economic performance. The combination of black liquor gasification (BLG) and chemical cycle combustion (CLC) can achieve high pulp production and clean production and has better economic performance. This research proposes an integrated CLC-BLG-MSSAQ pulp making process. Compared with conventional Kraft and MSSAQ processes, the CLC-BLG-MSSAQ process improves the energy efficiency by 6.2% and 12.2%, decreases carbon emissions by 0.62 t/ADt and 0.17 t/ADt. The economic analysis shows that under the scenario of USD 20/t CO2 -eq or above, the CLC-BLG-MSSAQ process, which has higher combustion efficiency and lower carbon emission, will cost the least compared with Kraft and MSSAQ processes. Highlights: A MSSAQ pulp making process integrated with chemical looping combustion is developed. The optimal operation condition of the proposed process is investigated. Energy efficiency is improved and carbon emission is reduced by integrating CLC with MSSAQ. Both economic and environmental insights of proposal process are provided.